Raman evaluation of graphene oxide dispersed in naphthenic oil - ALAN PASSERO; TAYNARA A. DE CARVALHO; NATALIA B. SANCHES; LIDIA M.S. MURAKAMI; JORGE CARLOS N. DUTRA; RITA DE CÁSSIA L. DUTRA (Anais da Academia Brasileira de Ciências)
Abstract Graphene oxide is a revolutionary material that enhances properties in electronics, automotive, civil construction, aerospace, and industrial sectors. Even added in low levels (0.1 – 5.0%), properly dispersed in polymer composites, it results in significant differences in mechanical, thermal, chemical, and electrical properties. Often, a suitable dispersant facilitate homogenization and provides stability in the fabrication process. However, there are few studies in the literature that assess graphene oxide dispersion. This paper presents methodologies for determining the graphene oxide content and its dispersion in naphthenic plasticizer in the presence of surfactant. A multivariate method, based on partial least squares regression and Raman spectroscopy, was used to determine the particle size and graphene oxide content in the graphene oxide /plasticizer system, with linearity (R2 > 0.99) and analytical error (> 0.29%). A laser diffraction methodology was developed for the dispersibility study. The results contribute to the state of the art of researching industrial aerospace solutions for polymeric systems containing graphene oxide.